2014
DOI: 10.4103/0975-9476.128848
|View full text |Cite
|
Sign up to set email alerts
|

Prakriti and its associations with metabolism, chronic diseases, and genotypes: Possibilities of new born screening and a lifetime of personalized prevention

Abstract: Ayurveda is one of the oldest health sciences of the world with concepts of tridosha and prakriti being core philosophies. These core concepts allow implementation of ways for not only personalized medicine and treatment but also personalized prevention. In the light of modern or current science, evidence has surfaced connecting the concepts of tridosha and prakriti with metabolic pathways, chronic diseases, and various genotypes. Such evidence has thrown up insights about the universality of Ayurvedic concept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 20 publications
2
51
0
Order By: Relevance
“…Prakriti is a set of physical, physiological and psychological attributes that are unique to an individual and can be 12 considered as a phenotypic phenomenon arising from a particular genotype. Human beings are classified into seven Prakriti types, the categorization being done based on certain attributes of the tridosha in their body.…”
Section: Prakriti -A Guide To Personalizationmentioning
confidence: 99%
“…Prakriti is a set of physical, physiological and psychological attributes that are unique to an individual and can be 12 considered as a phenotypic phenomenon arising from a particular genotype. Human beings are classified into seven Prakriti types, the categorization being done based on certain attributes of the tridosha in their body.…”
Section: Prakriti -A Guide To Personalizationmentioning
confidence: 99%
“…The detailed description of the phenotypic principles of health and disease state has been provided in the literature, but its potential has not been appreciated by modern genomic researchers. Thus, the chief aim of therapeutic MBTs is believed to ensure that tridosha remains in homeostatic state [22]. Some studies have found that chanting of maha mantra results in perfect harmony among the gunas besides reducing the stress and depression [23].…”
Section: Philosophical Aspect Of Mbtsmentioning
confidence: 99%
“…The Ayurvedic concept of prakriti or body constitution plays a vital role towards regulation of optimum health, that has shown a strong association with many psycho-physiological and biochemical parameters 13, 14. Since, there have been several limitations to prevent the progression of metabolic disorders, due to individual metabolic variability, 15 hence this study hypothesizes that intervention of yoga practices would regulate lipid metabolism with reference to specific prakriti. …”
Section: Introductionmentioning
confidence: 99%